Carbon Monoxide Fumigation Improved the Quality, Nutrients, and Antioxidant Activities of Postharvest Peach - Shaoying Zhang; Ying Li; Fei Pei (International Journal of Food Science)
Peaches (Prunus persica cv. Yanhong) were fumigated with carbon monoxide (CO) at 0, 0.5, 5, 10, and 20 μmol/L for 2 hours. The result showed that low concentration CO (0.5–10 μmol/L) might delay the decrease of firmness and titrable acid content, restrain the increase of decay incidence, and postpone the variation of soluble solids content, but treating peaches with high concentration CO (20 μmol/L) demonstrated adverse effects. Further research exhibited that exogenous CO could induce the phenylalnine ammonialyase activity, maintain nutrient contents such as Vitamin C, total flavonoid, and polyphenol, and enhance antioxidant activity according to reducing power and 2,2-diphenyl-1-(2,4,6-trinitrophenyl) hydrazyl radical scavenging activity. Treating peaches with appropriate concentration CO was beneficial to the quality, nutrients, and antioxidant activity of postharvest peaches during storage time. Therefore, CO fumigation might probably become a novel method to preserve postharvest peach and other fruits in the future.